ASIMETRI PERSEPSI PENILAIAN KINERJA DAN PERILAKU DIFUNGSIONAL TIM: TINJAUAN TERHADAP PROFIL TIM - Supia Yuliana (Universitas Ahmad Dahlan, 2012)
This paper introduced performance appraisal perception asymmetry construct on the team level management literature by integrated the performance appraisal perception and team behavior theories and researches. This paper proposed that performance appraisal perception asymmetry influenced the team dysfunctional behavior. Then, the author proposed that team structure might strengthened or weakened the performance appraisal perception asymmetry on the team dysfunctional behavior.